Band Gap Calculations for Thorium‐Doped LiCAF. Issue 10 (18th August 2022) - Pimon, Martin; Mohn, Peter; Schumm, Thorsten
Abstract: The large band gap insulator LiCaAlF6 (LiCAF) has been proposed as a possible host crystal for future realizations of a solid‐state based thorium‐229 nuclear clock, due to its excellent optical transmission in the vacuum ultraviolet range. To enable direct optical manipulation of the thorium isomeric state, the band gap has to remain larger than the nuclear excitation energy upon crystal doping. Here, a systematic search for possible charge compensation mechanisms, defect locations, and the emergence of other compounds, using density functional theory, is presented. Out of 535 optimized structures, the energetically most favorable arrangement is Th Al + V Li ′ Th_Al^+V_Li^′ with an estimated band gap of 11.4 eV. Evaluating relevant uncertainties of the used methods suggests that the doped material remains transparent at the 229 Th isomer energy for all investigated configurations. Abstract : A proposed solid state nuclear clock is composed of thorium doped into the large gap insulator LiCaAlF6 . Substitutional replacement of an aluminum atom and a neighboring lithium vacancy is energetically favored according to density functional theory calculations. It is estimated that the doped material remains transparent for the 229‐thorium isomer energy.